Influence of the homogeneous magnetic field of the laser-induced breakdown spectroscopy of copper plasma - Jasim, Marieam Ghreeb; Abbas, Qusay Adnan (Iraqi Journal of Science, 2018)
Copper plasma is generated with the existence of an external magnetic field and without its presence utilizing Nd:YAG laser (1064 nm ,9 ns) in different pulse laser energy which ranges from(100 to 400) mJ in a vacuum. Plasma parameter beta ) is least than 1, this indicates that the existence of magnetic field confinement effect is proven. Note that both the electron temperature and electron density increases with the laser pulse energy increasing , Both are higher in the presence of a magnetic field.